Energy scenarios: a review of methods, uses and suggestions for improvement. (5th July 2007) - Nielsen, Stefan Kruger; Karlsson, Kenneth
Scenarios are used in research, foresight, planning, policy-making and business strategy within the energy domain. There is no common theoretical and methodological framework for making scenario analysis. Rather, definitions and methodologies are most often tailored for specific uses. Scenarios are used for three overarching purposes: For predicting, exploring and anticipating future energy systems. Energy scenarios most often involve economic/engineering modelling of the energy system relying on uncertain projections, expectations, visions or hope for future economic or technical developments thereby lacking a detailed argumentation for the specific social and political conditions under which the scenarios may likely unfold. Energy scenario studies may be improved by focusing more on describing short-term policies and actions that may possibly lead to the future states taking into consideration the role of market conditions as well as lifestyle and social developments.